Risk Analysis Using Multi-Attribute Failure Mode Analysis Approach in Mybeb Social Payment Application - Bob Maulana Adam; Zeplin Jiwa Husada Tarigan (Institut Teknologi Adhi Tama Surabaya, 2022)
MyBeb is a social payment application owned by one of the FinTech companies in the Sidoarjo area, East Java Province. Mybeb itself is an application that provides social media features as well as payments. In running the product, several obstacles and operational risks arise that have not been handled properly, and not a few users have not been properly educated in the use of this application. This study aims to identify risk priorities and corrective actions that must be taken using the MAFMA method. The method is to detect failure points that have great potential to be overcome. Then get the results and benefits of the analysis method that will affect the company using the methods. From the methods, the risk with the highest value was at the risk of the P10 value, which was 0.482. At the same time, the lowest risk is at P1 risk with a risk level value of 0.251. Then for managerial implications for the proposed improvement to the method with the highest risk level at P10 risk, a page for a list of friends using referral links from users is given to those who have done uploading profile photos.